THE BIOLOGY OF CANADIAN WEEDS. 2. SPIRAEA LATIFOLIA - HALL, I. V.; MURRAY, R. A.; JACKSON, L. P. (Canadian Journal of Plant Science, 1974)
Spiraea latifolia (Ait.) Borkh., broad-leaved meadowsweet (Rosaceae), is a weed of pastures, lowbush blueberry (Vaccinium angustifolium Ait. and V. myrtilloides Mich.) fields and cranberry (V. macrocarpon Ait.) bogs of Eastern Canada, especially where soil moisture content is high during the growing season. Where S. latifolia occurs, other vegetation is lacking or depressed. Much time is lost in harvesting lowbush blueberries due to jamming of the S. latifolia stems among the tines of the rake or in cranberries due to mechanical damage to the harvesters. In Canada, S. latifolia occurs in Newfoundland, Prince Edward Island, Nova Scotia, New Brunswick, Quebec, Ontario, and Manitoba.